Optimization of cell culture‐derived influenza A virus particles purification using sulfated cellulose membrane adsorbers. Issue 1 (16th October 2017) - Fortuna, Ana Raquel; Taft, Florian; Villain, Louis; Wolff, Michael W.; Reichl, Udo
Abstract: Downstream processing remains one of the biggest challenges in manufacturing of biologicals and vaccines. This work focuses on a Design of Experiments approach to understand factors influencing the performance of sulfated cellulose membrane adsorbers for the chromatographic purification of a cell culture‐derived H1N1 influenza virus strain (A/Puerto Rico/8/34). Membranes with a medium ligand density together with low conductivity and a high virus titer in the feed stream resulted in optimum virus yields and low protein and DNA content in the product fraction. Flow rate and salt concentration in the buffer used for elution were of secondary importance while membrane permeability had no significant impact on separation performance. A virus loss of 2.1% in the flow through, a yield of 57.4% together with a contamination level of 5.1 pgDNA  HAU −1 and 1.2 ngprot  HAU −1 were experimentally confirmed for the optimal operating point predicted. The critical process parameters identified and their optimal settings should support the optimization of sulfated cellulose membrane adsorbers based purification trains for other influenza virus strains, streamlining cell culture‐derived vaccine manufacturing.